(untitled) (Research, Society and Development, 2020)
The context of the pandemic COVID-19 created an innovative emergency scenario in schools, where it gave way to remote education. Today, much is heard about in synchronous and asynchronous online classes as an emergency measure in this period when the World Health Organization advises social isolation. As schools around the world make the transition to online learning during the pandemic, public school students in rural regions are unable to keep up with this teaching model and, alternatively, receive printed materials as remote activities. Thus, without access to online platforms, it is impossible for students to contact teachers to answer their questions, which can result in losses in learning. In this sense, we aim to assess the impact of remote activities due to the Covid-19 pandemic on rural education students in five cities in northern Minas Gerais. For that, we evaluated some factors that expose these difficulties of remote education in the field. Data collection was performed using two techniques: interview and focus group. Interviews were conducted with 294 responsible for students from rural schools. Our hypothesis (H0) is that there is precarious access to communication technologies, infrastructure and food in the homes of most students who are part of rural education in northern Minas Gerais. As a result, we partially accept the hypothesis and conclude that, although remote activities in these rural areas can be considered important for keeping students active, such activities alert to impairments in learning.